Environmental DNA metabarcoding elucidates patterns of fish colonisation and co‐occurrences with amphibians in temperate wetlands created for biodiversity. (26th July 2021) - Kačergytė, Ineta; Petersson, Erik; Arlt, Debora; Hellström, Micaela; Knape, Jonas; Spens, Johan; Żmihorski, Michał; Pärt, Tomas
Abstract: Wetlands are biodiversity hotspots that provide several essential ecosystem services. On a global scale, wetlands have greatly declined due to human activities. To counteract wetland loss, created wetlands are used as a conservation tool to facilitate biodiversity and provide habitats mainly for birds and amphibians. Fishes are likely to colonise the created wetlands and potentially affect the diversity and occurrence of amphibians. Still, species occurrence data for fish in created wetlands are largely lacking. Using eDNA metabarcoding, we investigated occurrence and co‐occurrence patterns of fish and amphibian communities in 52 wetlands (some of which are ponds) created to benefit mainly bird and amphibian communities in south‐central Sweden. Altogether, 17 fish and five amphibian species were detected in the created wetlands out of the 32 fish and six amphibian species found in the regional species pool. Amphibians were less common in wetlands physically connected to other wetlands. Connected wetlands were more fish‐rich than isolated ones, suggesting potential fish avoidance. Additionally, the amphibian community occupied a narrower environmental niche compared to the fish community. Nevertheless, we observed only five statistically significant negative fish–amphibian species co‐occurrences (out of 14 species considered). Even though our results suggest amphibian avoidance/exclusion from the created biodiversity wetlands, they also show that fish and amphibians frequently co‐exist. Increased habitat heterogeneity in terms of water vegetation, size, shape, and structure of the wetland could be possible factors enabling the co‐existence of these two taxa. With this study, we contribute to the general knowledge of fish occurrence patterns in created biodiversity wetlands. By comparing the frequencies of fish occurrence in natural and created wetlands, we have shown that there was some mismatch in what is common in natural compared to created wetlands. This mismatch probably comes from species‐specific habitat requirements, stocking, and differences in detectability when using eDNA metabarcoding (small species detected) versus conventional multi‐mesh gill‐net methods (small species missed). Therefore, our results obtained using eDNA metabarcoding can complement the pre‐existing knowledge of amphibian and fish associations and increase our understanding of how to create wetlands to facilitate biodiversity of several taxa.